INTERACTIVE EDUCATION FOR BETTER DENTAL HEALTH: A COMMUNITY SERVICE EXPERIENCE IN SIDOARJO - Khoirul Fikriyah; Diani Arditya Siwi Widhiatmi; Amalia Hartiningrum (Journal of Community Research and Engagement, 2026)
Background: The Clean and Healthy Living Behavior (CHLB) movement is a fundamental principle that needs to be implemented in daily life. The background to this activity was based on the importance of preventing tooth decay from an early age, which has been proven to impact child growth and development. Objective: The goal was to provide education on CHLB, particularly regarding maintaining dental health in early childhood. Method: The current community service program was implemented at RA An-Nur RT 37, Sidokepung Village, Buduran, Sidoarjo. The methods used included initial observation, material development, interactive learning media development, lesson plan development, and outreach. The outreach was attended by 37 group B students, using an interactive approach consisting of illustrated stories, group practice, and fun mini-games. Results: The results showed an increase in students’ understanding of the importance of maintaining dental health, the appropriate time to do so, and their understanding of choosing healthy foods for teeth. CHLB outreach using interactive educational methods has proven effective in increasing early childhood awareness of dental health while fostering healthy habits from an early age. Conclusion: This activity successfully demonstrated that utilizing an interactive educational approach, incorporating illustrated stories, group practice, and mini-games, is highly effective in increasing early childhood awareness regarding dental health.